2023
DOI: 10.1007/s10068-023-01289-y
|View full text |Cite
|
Sign up to set email alerts
|

Wheat sprouts (Triticum aestivum Linn.) cultured by a smart farm system ameliorate NAFLD through the AMPK-mediated SREBP signaling pathway

Abstract: Wheat is cultivated worldwide and is the most widely distributed food crop. Wheat is a staple crop in many countries. However, the effects of various cultivation methods on the efficacy of wheat sprouts have not been determined. This study investigated wheat sprouts obtained using a standardized smart farm system (WS-S) to improve the effects of non-alcoholic fatty liver disease (NAFLD) and molecular mechanism. Wheat sprouts significantly attenuated the accumulation of lipid droplets in FFA-induced HepG2 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…In this sense, the elevation of high-density lipoprotein as a result of feeding hydroponic wheat sprouts here would avoid the accumulation of cholesterol in peripheral tissues impacting positively on ewes’ health and welfare. Chang et al [ 17 ] elucidated that wheat sprouts could significantly attenuate the accumulation of lipid droplets in liver cells and non-alcoholic fatty liver disease-induced mice through the AMPK pathway activity, accompanied by the decrease of total cholesterol in the blood. Another study indicated that the extraction of wheat sprouts could suppress acetaminophen-induced hepatotoxicity in mice, manifested by inhibiting oxidative liver damage and reducing the expression of inflammatory cytokines [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the elevation of high-density lipoprotein as a result of feeding hydroponic wheat sprouts here would avoid the accumulation of cholesterol in peripheral tissues impacting positively on ewes’ health and welfare. Chang et al [ 17 ] elucidated that wheat sprouts could significantly attenuate the accumulation of lipid droplets in liver cells and non-alcoholic fatty liver disease-induced mice through the AMPK pathway activity, accompanied by the decrease of total cholesterol in the blood. Another study indicated that the extraction of wheat sprouts could suppress acetaminophen-induced hepatotoxicity in mice, manifested by inhibiting oxidative liver damage and reducing the expression of inflammatory cytokines [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Applying IoT technology during germination can increase seed survival rate and create conditions conducive to better seed germination [17]. There has been a marked increase in the cultivation of sprout vegetables in smart farms using IoT, the diversity of which is increasingly expanding to include the sprouts of crop plants such as peanut, radish, and wheat [18][19][20]. Peanut (Arachis hypogaea) is an annual herbaceous legume in the Fabaceae family; its nuts are a rich source of nutrients, including carbohydrates, proteins, fibers, fats, phosphorus, resveratrol, and flavonoids [21,22].…”
Section: Introductionmentioning
confidence: 99%